TRPV1 activity and substance P release are required for corneal cold nociception - Fengxian Li (Nature Portfolio, 2019)
The eye shows protective responses to noxious stimuli including cold. Here, the authors show that TRPV1, found co-expressed on TRPM8 + fibres in the cornea, is necessary for cold nociception in the eye.